Determinan pertumbuhan industri besar dan menengah di Provinsi Jambi - Syaiful Rachman; Arman Delis; Siti Hodijah (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2015)
The study aims to analyze the factors that influence the growth of large and medium scale industrial output in Jambi Province. The data used are secondary data of Jambi Province during the period 2000 - 2014. Data were analyzed descriptively and used multiple regression models. The results of this study found that: 1) large-scale industrial value added for food and beverage groups and wood and rattan industries was significantly affected by investment. Whereas the rubber and plastic industry groups are significantly affected by the number of workers; 2) medium-scale industrial value added for all industry groups (food and beverages, textiles, wood and rattan, rubber and plastics, goods and metals) influenced by the amount of labor and investment.